(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:The signs and symptoms of acute appendicitis vary according to the site of the appendix; and absence of tenderness in the right iliac fossa dose not exclude appendicitis like in postileal, subhepatic and pelvic appendix. Even Alvarado scale zero is not excluding the diagnosis of acute appendicitis. Objective:To study the incidence of delayed appendectomy and its relation to the anatomical variation of the appendix and its morbidity. Methods: A prospective study for patients whom underwent appendectomy for acute appendicitis during the period from-June 2009 to June-2010. The appendix of all the patients was submitted to histopathological examination and was proved to be acutely inflamed. The patients were divided into two groups according to the time interval from the onset of the first symptom to the time of appendectomy. In group A, this interval was more than 72 hours; while in group B it was less than 72 hours. Results:Group A includes 35 patients; while group B include 201 patients. The anatomical site of the appendix in group A was very significant in delayed decision of appendectomy in postileal appendix (P=0.0001), subhepatic appendix (P=0.0004), and significant in retrocecal appendix (P=0.017); but it is not significant in pelvic appendix (P=0.88), paracecal appendix (P=0.83) and preileal appendix (P=0.95). Patients in group A had longer hospital stay due to complications 35 (100%) generalized peritonitis and 3 (8.57%) patients were died due to septic shock which is significant (P=